ANALISIS KINERJA SATKER PSDKP PEKALONGAN DILIHAT DARI ASPEK PERIKANAN TANGKAP DI PELABUHAN PERIKANAN NUSANTARA (PPN) PEKALONGAN - Anggityarini, Stella; Rosyid, Abdul; Boesono, Herry (Journal of Fisheries Resources Utilization Management and Technology, 2013)
PSDKP Unit Pekalongan is one of the public organizations that provides services, hence this factor affected PSDKP Unit performance towards the fishers entrepreneur. The purposes of study were to find out PSDKP Unit Pekalongan’s performance, analyze PSDKP Unit services quality towards fishing entrepeneur satifaction in PSDKP Unit Pekalongan and to analyze the research result to find solution from the problem that faced by the Satker PSDKP Pekalongan. The reseach method used in this reseach was descriptive method, while the sampling method used was purposive sampling by the number of samples taken 30 respondents. Data analysis methods used are Servqual Analysis and Cartesian Diagram. The result from the fishing’s services quality research were 79,40%. Servqual score analysis can be seen that expectation is 1472, while the perception is 1176, so that the Servqual score that can be obtained was -296. Cartesian Diagram analysis showed that power responsiveness dimension is in A quadrant it meant become first priority, empathy dimension in B quadrant it meant maintain performance, direct evidence dimension in C quadrant was inlow priority and reliability and assurance dimension in D quadrant was in overcome priority.